Challenges Faced by Youths in Institutional Care Centers in Their Transit to Adulthood: A Case of One Child Care Institution in Zimbabwe - Muguwe, Emely (Globeedu Group, 2022)
The paper explores challenges faced by youths who age-out of institutional care and their transition to adulthood in Zimbabwe. Two informants, social welfare officers and a matron, and three youths aging out of institutional care were purposively selected and participated in a phenomenological qualitative study, through face-to-face interviews. Findings revealed that youths who age-out of care experience a number of challenges regardless of the imparted skills for life outside care institutions. Some of these challenges include unemployment, homelessness, poor health care, early pregnancies and in some cases extreme poverty after leaving care. Findings also reveal that some of them get the opportunity to go to college or to university if they obtain good results at ‘O’ or ‘A’ levels. The other finding is that they are not just chucked out of institutional care, but transition is gradual. For a small percentage of the youths the challenges are turned into opportunities, but for the larger percentage life after care is a struggle. The implications are that the cycle of homelessness, poverty and disease continues to haunt some of those children who move out of care when they turn eighteen years and above before they are integrated back into society. The paper recommends that the process of leaving care should be prepared more intensely mainly through foster care and through the re-integration process